2x-9+6x=-3(3+5x)

Simple and best practice solution for 2x-9+6x=-3(3+5x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-9+6x=-3(3+5x) equation:


Simplifying
2x + -9 + 6x = -3(3 + 5x)

Reorder the terms:
-9 + 2x + 6x = -3(3 + 5x)

Combine like terms: 2x + 6x = 8x
-9 + 8x = -3(3 + 5x)
-9 + 8x = (3 * -3 + 5x * -3)
-9 + 8x = (-9 + -15x)

Add '9' to each side of the equation.
-9 + 9 + 8x = -9 + 9 + -15x

Combine like terms: -9 + 9 = 0
0 + 8x = -9 + 9 + -15x
8x = -9 + 9 + -15x

Combine like terms: -9 + 9 = 0
8x = 0 + -15x
8x = -15x

Solving
8x = -15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15x' to each side of the equation.
8x + 15x = -15x + 15x

Combine like terms: 8x + 15x = 23x
23x = -15x + 15x

Combine like terms: -15x + 15x = 0
23x = 0

Divide each side by '23'.
x = 0

Simplifying
x = 0

See similar equations:

| [1+3c]-18=-8 | | 9+8m=-3 | | 4-3w=8.5 | | 3y-6x=-33 | | F[x]=2x+12 | | -10w=15 | | x(x+4)=6(2) | | 9=v+6-2 | | (5x)=-18 | | (2x+20)=(3x-10) | | 3(2x+1)-5x=2(x+1)-3 | | (2x-20)=(3x-10) | | 15=12x^2+24x | | 4d+8-2d=6d-10 | | -12x+2y=x+2 | | 7xy-4xy+2xy+6xy+3xy-7xy= | | 14x-(3x-7)=40 | | f(n)=2*f(n-1) | | 3(3z+1)-8=40 | | -1440=-15(-15x-29) | | 8u-1=8 | | (6+k)+12=23 | | 3(2x-7)-4(x-1)= | | 2h+10=66 | | 2h+10=66 | | y-8+124=180 | | -41=5x+9 | | -1440=-15(-15x-21) | | 1.4a+10=17 | | 6x+13=5x | | n+36=5m | | (X-3)(x+4)=x^2-5x+20 |

Equations solver categories